2015
DOI: 10.1007/s11192-015-1629-z
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the intellectual structure of library and information science based on formal concept analysis

Abstract: Detecting intellectual structure of a knowledge domain is valuable to track the dynamics of scientific research. Formal concept analysis (FCA) provides a new perspective for knowledge discovery and data mining. In this paper we introduce a FCA-based approach to detect intellectual structure of library and information science (LIS). Our approach relies on the mathematical theory which formulates the understanding of ''concept'' as a unit of extension (scholars) and intension (keywords) as a way of modelling the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The research specialty of evaluative bibliometrics has been studied repeatedly with scientometric mapping techniques [ 45 49 ]. This literature locates the area within the broader disciplinary category of library and information sciences [ 50 54 ]. Different methodological approaches have been pursued to identify substructures based on delineations, such as search terms or publications in key journals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research specialty of evaluative bibliometrics has been studied repeatedly with scientometric mapping techniques [ 45 49 ]. This literature locates the area within the broader disciplinary category of library and information sciences [ 50 54 ]. Different methodological approaches have been pursued to identify substructures based on delineations, such as search terms or publications in key journals.…”
Section: Methodsmentioning
confidence: 99%
“…These studies converge in ECA being a core bibliometric research area since the introduction of the Science Citation Index (SCI) in the 1960s; as such, it can be distinguished from “visualization of knowledge domains” and “webometrics” [ 45 , 47 ]. In addition, “impact factor,” “h-index,” and “journal impact” are core keywords associated with citation analysis [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…The other interesting finding of the study was the change of focus from the LIS organization to end-user and system development along with increased attention to evaluation and experimentation. Liu et al (2015) reviewed the 10,648 bibliographic records published in 16 leading LIS journals between 2001 and 2013. The paper used the formal concept analysis method to identify the intellectual structure of LIS.…”
Section: International Lis Research Trendsmentioning
confidence: 99%
“…This approach enables researchers to examine a larger corpus of text data than content analysis and bibliometric methods. Liu et al (2015) investigated the intellectual structure of library and information science using the formal concept analysis (FCA) method. By analyzing the papers published in 16 prominent journals in the LIS domain from 2001 to 2013, the authors identified nine main LIS research themes: bibliometrics, scientometrics, and informetrics; citation analysis; information retrieval; information behavior; libraries; user studies; social network analysis; information behavior; and webometrics.…”
Section: Model-based Approachesmentioning
confidence: 99%
“…Content analysis was also a widely applied approach (Järvelin and Vakkari 1993;Koufogiannakis et al 2004;Blessinger and Frasier 2007). Today, an increased interest has shown in using model-based approaches to explore the intellectual structure of a domain (Sugimoto et al 2010;Liu et al 2015;Figuerola et al 2017). The method allows researchers to examine large document collections.…”
Section: Introductionmentioning
confidence: 99%